Pemberdayaan Masyarakat Melalui Pemetaan Lahan Petani Pala di Kabupaten Fakfak - Dessy Eka Kuliahsari; Reski Rahman Sriwijaya; Muhammad Ayyub Syamsul (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Indonesia is one of the world's largest producers and exporters of nutmeg seeds and mace. The main markets for Indonesia's nutmeg exports are Vietnam, the United States, the Netherlands, Germany, and Italy. Nutmeg is a superior commodity for the Fakfak community and has great potential to continue to be developed. However, the potential development still needs to be improved. The problem is that there needs to be a village potential map which causes potential village management to be hampered. The solution to this problem is necessary to map the land of nutmeg farmers. The purpose of this community service is to obtain a map of the distribution of nutmeg in the Fakfak district. This community service method includes preparation, data collection directly on farmers' land, making distribution maps, and sharing nutmeg distribution maps. Preparation includes the division of regions and teams as well as data collection. Data retrieval is done directly to get accurate coordinates. Making maps using experts based on the coordinate points obtained. Distribution map sharing is given to partners and related agencies. The results are the output map of the distribution of nutmeg in the districts of Fakfak Regency. Community service activities need to be continued because they can optimize the potential of Fakfak Regency.